On the gracefulness of the digraphs n - C→21 - Jinsiqintuya, Jirimutu, (Utilitas Mathematica, 2012)
A digraph D(V, E) is said to be graceful if there exists an injection f : V(D) → {0, 1, . . . , |E|} such that the induced function f' : E(D) → {1, 2, . . . , |E|) which is defined by f'(u, v) = [f(v) - f(u)] (mod (|E| +1)) for every directed edge (u, v) is a bijection. Here, f is called a graceful labeling (graceful numbering) of digraph D(V, E), and f' is called the induced edge's graceful labeling of digraph D(V, E). In this paper we discuss the gracefulness of the digraph n - C→m and prove the digraph n - C→21 is graceful for even n.